2007 European Control Conference (ECC) 2007
DOI: 10.23919/ecc.2007.7068525
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control of an experimental water canal

Abstract: This paper presents the first experimental results of a model predictive controller designed to control the water levels of a modern automated water canal, located at the University ofÉvora, Portugal. The controller is able to correctly handle known-in-advance water offtakes, while considering the most relevant physical constraints of the experimental setup. The dynamic model used is based on discretized Saint-Venant equations linearized for the steady-state regime taking into account the hydraulic structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This gives a very good performance, particularly in simulations, but at the cost of a higher computational power required as the size of the control problem is larger than in the decentralized or distributed case, in which only a partition of the overall problem is considered at a time (see also Weyer (2008) for a discussion on differences between centralized and decentralized control strategies for irrigation canals). The common factor in ), van Overloop et al (2005 and Silva et al (2007) is that, as a new set of control actions needs to be found in every control step, the volume of communication between the control center and the local sites may exceed the practicable amount, which may result in the control signal not being conveyed to the gates, and consequently in the canal not being managed properly.…”
Section: Previous Work On Control Of Irrigation Canalsmentioning
confidence: 95%
See 1 more Smart Citation
“…This gives a very good performance, particularly in simulations, but at the cost of a higher computational power required as the size of the control problem is larger than in the decentralized or distributed case, in which only a partition of the overall problem is considered at a time (see also Weyer (2008) for a discussion on differences between centralized and decentralized control strategies for irrigation canals). The common factor in ), van Overloop et al (2005 and Silva et al (2007) is that, as a new set of control actions needs to be found in every control step, the volume of communication between the control center and the local sites may exceed the practicable amount, which may result in the control signal not being conveyed to the gates, and consequently in the canal not being managed properly.…”
Section: Previous Work On Control Of Irrigation Canalsmentioning
confidence: 95%
“…In contrast to the aforementioned decentralized or distributed schemes, centralized algorithms as studied in ), van Overloop et al (2005), van Overloop et al (2010 and Silva et al (2007) consider the canal as one entity with control actions for the gates provided by a central controller looking at the whole system, not at individual subsystems separately. This gives a very good performance, particularly in simulations, but at the cost of a higher computational power required as the size of the control problem is larger than in the decentralized or distributed case, in which only a partition of the overall problem is considered at a time (see also Weyer (2008) for a discussion on differences between centralized and decentralized control strategies for irrigation canals).…”
Section: Previous Work On Control Of Irrigation Canalsmentioning
confidence: 96%
“…• it can be easily integrated into model based control strategies (Martinez, 2007) (Silva et al, 2007) opening the gate to its inclusion in fault tolerant control applications (Blanke et al, 2006) (Isermann, 2006) (Bedjaoui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, the distributed control strategies introduced in, e.g., [1,5,9,15] as well as the centralized control strategies introduced in, e.g., [22,27,28] may turn out to rely too heavily on the communication links, thus being rendered impracticable for a real-life application. This is caused by the requirement of these controllers to communicate in every control step during their operation either with each other in case of distributed control, or with a control center in case of centralized control.…”
Section: Motivation and Contributionsmentioning
confidence: 99%